2018
DOI: 10.26717/bjstr.2018.09.001798
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Mechanical and EMG Variables Assessed During Concentric Bench Press Exercise Against Different Submaximal Loads

Abstract: The assessment of specific neuromuscular performance qualities provides relevant insight into the training status of an individual in relation to the sport requirements. This information is crucial for detecting potential deficiencies in strength and power capacities and, therefore, for designing individualized resistance training programs aimed at improving physical performance [1].Skeletal muscle function can be evaluated using a wide variety of tests, which should provide reliable, valid, sensitive and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
(89 reference statements)
1
5
0
1
Order By: Relevance
“…Similar results were reported by García‐Ramos et al (2018) during the traditional BP performed using the concentric‐only and eccentric‐concentric techniques. In line with the aforementioned studies (García‐Ramos, Haff, Padial, et al, 2018; García‐Ramos, Pestaña‐Melero, Pérez‐Castilla, et al, 2018; Yáñez‐García et al, 2018), the Vmax was also the most reproducible variable for all the grip widths evaluated in the present study. Previous studies have suggested that the lower reliability observed for mean values could be caused by the difficulty to determine the start of the concentric phase (García‐Ramos, Haff, Jiménez‐Reyes, et al, 2018; García‐Ramos, Haff, Padial, et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar results were reported by García‐Ramos et al (2018) during the traditional BP performed using the concentric‐only and eccentric‐concentric techniques. In line with the aforementioned studies (García‐Ramos, Haff, Padial, et al, 2018; García‐Ramos, Pestaña‐Melero, Pérez‐Castilla, et al, 2018; Yáñez‐García et al, 2018), the Vmax was also the most reproducible variable for all the grip widths evaluated in the present study. Previous studies have suggested that the lower reliability observed for mean values could be caused by the difficulty to determine the start of the concentric phase (García‐Ramos, Haff, Jiménez‐Reyes, et al, 2018; García‐Ramos, Haff, Padial, et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have suggested that the lower reliability observed for mean values could be caused by the difficulty to determine the start of the concentric phase (García‐Ramos, Haff, Jiménez‐Reyes, et al, 2018; García‐Ramos, Haff, Padial, et al, 2018). It should be noted that MV values were used in this study instead of MPV values because they can be obtained with a higher reliability during the BP exercise (García‐Ramos, Haff, Jiménez‐Reyes, et al, 2018; García‐Ramos, Pestaña‐Melero, Pérez‐Castilla, Rojas, et al, 2018; Yáñez‐García et al, 2018) and they can be easy measured by most of the commercially available devices (e.g. linear position transducers, mobile apps or accelerometers) (Pérez‐Castilla et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations